Anhidrotic ectodermal dysplasia and immunodeficiency: the role of NEMO. Issue 4 (1st April 2003) - Carrol, E D; Gennery, A R; Flood, T J; Spickett, G P; Abinun, M
Abstract : Anhidrotic (hypohidrotic) ectodermal dysplasia associated with immunodeficiency (EDA-ID; OMIM 300291) is a newly recognised primary immunodeficiency caused by mutations in NEMO, the gene encoding nuclear factor κB ( N F-κB) e ssential mo dulator, NEMO, or inhibitor of κB kinase (IKK-γ). This protein is essential for activation of the transcription factor NF-κB, which plays an important role in human development, skin homoeostasis, and immunity.